Joachim Bouvet’s interpretation of Zhouyi and his mathematical model : research on Joachim Bouvet’s Chinese manuscripts of Yijing in the Apostolic Vatican Library collection - Mu, Xiaofeng (Nanyang Technological University, 2020)
The westward spread of Zhouyi周易 (or Yijing易经) and the Missionaries’ Yijing-study coincided with the prelude of modern Catholic missions in China and became entangled with the ups and downs of their development over a period of 200 years. Jesuit missionary Fr. Joachim Bouvet白晋 (1656-1730) undoubtedly was one of the most representative and influential figures of such academic pursuits during the reign of Emperor Kangxi (1654-1722). Bouvet’s study of Zhouyi was gradually done under the guidance of Kangxi himself. Fruits of such painstaking endeavor are the sixteen writings authored by Bouvet in the Chinese language conserved in the Vatican Apostolic Library.